Income inequality and development in Malaysia - Pua, Vivien Fei Wen (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study is to examine the relationship between income inequality and development across Malaysian states by using yearly data which cover the period ranging from 1984 to 2012. A panel analysis is used to run the estimation in 13 of Malaysian states. The methodologies that have been employed in this study included Breusch-Pagan Lagrange Multiplier Test, Hausman specification test and panel regression. A scattered graph between GDP per capita and GINI coefficient will be plotted to test the existence of Kuznets inverted-U curve hypothesis. The empirical findings show the existence of Kuznets inverted-U curve in seven out of thirteen of Malaysian states. There is a negative relationship between income inequality and development in Malaysia.